Identifying the most reliable and valid bladder health screening tool: a systematic review. Issue 17 (13th August 2020) - Booth, Lorna; Skelton, Dawn A.; Hagen, Suzanne; Booth, Joanne
Abstract: Purpose: Lower urinary tract symptoms are common in advancing age and a major cause of disability through avoidance of activity and social engagement. This systematic review aimed to identify the most valid and reliable brief screening tool for these symptoms or bladder problems, to incorporate into a health promotion programme for older adults to facilitate discussion about self-management. Method: Review eligibility criteria included studies published between 1990 and November 2018, reporting the validity, reliability and/or acceptability of bladder health screening tools. Six electronic databases were searched. Results: Twenty-two studies were included. Three screening tools met the criteria: International Prostate Symptom Score (IPSS); International Consultation on Incontinence Questionnaire Urinary Incontinence Short-Form; Bladder Control Self-Assessment Questionnaire (B-SAQ). Test–retest reliability for total scores of the IPSS and International Consultation on Incontinence Questionnaire Urinary Incontinence Short-Form was acceptable. All three questionnaires showed evidence of acceptable levels of internal consistency and of convergent validity. Conclusion: Having favourable psychometric scores compared to the B-SAQ and for ease of use and trustworthiness of a simple questionnaire, the IPSS and International Consultation on Incontinence Questionnaire Urinary Incontinence Short-Form met the criteria for recommendation for raising awareness and bladder health promoting interventions to reduce associated disability. Implications for Rehabilitation: Lower urinary tract symptoms are common in advancing age and a major cause of disability through avoidance of activity and social engagement. Lower urinary tract symptoms can be prevented or improved through self-management strategies. Help-seeking levels for lower urinary tract symptoms is low but could be improved through continence promotion interventions. The International Prostate Symptom Score and the International Consultation on Incontinence Questionnaire – Urinary Incontinence Short Form are bladder health screening questionnaires which would be appropriate to use as part of a continence promotion intervention to help prompt discussions and raise awareness and subsequently improve symptoms and associated disability.